Web-Based Inventory Application Development for PT. Palugada Indonesia - Justin A. Haratua; Andree E. Widjaja; Kusno Prasetya; Hery Hery (IJNMT (International Journal of New Media Technology), 2021)
PT. Palugada Indonesia still records their transactions and inventory of goods in traditional ways, which could result in some errors caused primarily by human interventions. The aim of this research is to assist PT. Palugada Indonesia to control their inventory through an information system. Specifically, a web-based application that can process product data, supplier data, customer data, user data and transaction data was purposefully developed in this study. In addition, the developed application has notification and sales forecast features. These features are expected to further assist PT. Palugada Indonesia to control their inventory optimally. Moreover, the application also has some other useful features, for instance in displaying more informative data, by bringing up sales forecasts and notifications. The developed application was modeled using UML diagram 2.0 and developed using HTML, PHP, and MySQL database. Index Terms—inventory; web-based application; saels forecast; PT. Palugada Indonesia